Comment on Ulrich Brand et al., "From planetary to societal boundaries". Issue 1 (9th December 2022) - Alcott, Blake
Abstract: While agreeing with the science of the "planetary boundaries" work of Johan Rockström and colleagues, as well as their normative support for political measures to restrict the human economy to the realm inside those boundaries, a recent article by Brand et al. in this journal criticizes the former mainly on the grounds that they pay too little attention to capitalism's alleged growth imperative and to certain technocratic and/or global-only interpretations to which the planetary boundaries framework is dangerously open. I argue that Brand et al. do not refute or disagree with Rockström et al., as they claim, but rather point out what the latter omit. Rockström et al. consciously limited the scope of their work, and therefore a polemical criticism of their omissions is not justified. I also argue against the centrality of the concept "capitalism" in Brand et al.'s critique, claiming that growth/degrowth analyses and strategies for degrowth do not need to go into the issues of capitalism vs. alternatives to it because drivers of growth are deeper than such systems concepts allow us to investigate. Capitalism and socialism do explain some things, but mainly, they themselves have to be explained in a full analysis of both over-growth and what to do about it politically in democracies. Shifts toward acceptance of material-energy limitations must be psychological and social, whatever the economic system's rules on such things as ownership of the means of production, economic-power equality, the money system, or macro-economic incentives to growth.